Small Medium Enterprises Building a Sustainable Competitive Advantage Through the Application of Cloud Computing Services - Nardone, Kevin (2017)
Small to medium sized enterprises (SMEs) have been competing with big businesses for market space since the start of capitalism. However, until technological resources such as cloud computing were developed and affordably accessible, their efforts to compete often proved futile. This study used a qualitative model focusing on four samples from well-established SMEs with varying backgrounds. Semi-structured interviews were conducted with each, and the insights gained from these interviews were compared with the findings of existing literature. The purpose of this study is to show the impact cloud computing had on improving SMEs’ ability to keep up with larger, asset-rich companies, while presenting a resource-based view of SMEs’ sustainable competitive advantages.